Trends, Causes, Morbidity, and Mortality Analysis of Road Traffic Accidents in Karnali Province, Nepal: A Three-Year Retrospective Study - Khadka, Rabin; Tiwari, Bhuwaneshwar; Acharya, Upendra Prasad; BC, Udaya Bahadur; Adhikari, Rita; Thapa, Kanchan (Asian Journal of Population Sciences, 2024)
Globally, Road Traffic Accidents (RTA) are one of the leading causes of morbidity and mortality. Low and middle-income countries account for more than ninety per cent of the total global RTA deaths. Early response and prompt rescue can prevent mortality and morbidity. Nepal's accidents arise from substandard roads, vehicle safety, and reckless driving. This study aimed to examine trends, causes, morbidity, and mortality from RTA in Karnali province, Nepal. Secondary data analysis encompassed ten Karnali districts, utilizing records from the Province Traffic Police between July 17, 2019, and July 16, 2022. Motorcycles/scooters, constituting 77.27 per cent (13,127) of registered vehicles, dominated with 932 RTAs during the study, causing 1,200 minor injuries, 719 major injuries, and 392 fatalities. Males constituted 70.87 per cent of fatalities (6.86% <16 years), and females accounted for 21.15 per cent (1.09% <16 years). The age group 20-25 years accounted for 163 (17.19%) of the deaths, followed by 25-30 years 168(17.72%). Non-license holders were involved in 363(33.83%) of accidents within the study period. In Karnali, the overall count of RTAs, injuries, and fatalities increased, driven mainly by high speed and mechanical errors. Surprisingly, while two-wheeler accidents were common, bus accidents resulted in a significant number of deaths, impacting individuals aged 20-30 and children.